Connectors for electrical and electronic equipment. Product requirements. Power connectors. Detail specification for 2P 130 A, 1 000 V plus 2P 5 A 50 V rectangular housing shielded connectors with IP65/IP68 degree of protection when mated and locked, and IPXXB when unmated Part 8-109, (31st May 2023) - British Standards Institution,
No abstract available